Biogeographic distribution of autotrophic bacteria was more affected by precipitation than by soil properties in an arid area - Wang, Ying; Huang, Yimei; Zeng, Quanchao; Liu, Dong; An, Shaoshan (Frontiers in Microbiology, 2023)
Introduction: Autotrophic bacteria play an important role in carbon dioxide fixation and are widespread in terrestrial ecosystems. However, the biogeographic patterns of autotrophic bacteria and the driving factors still remain poorly understood. Methods: Herein, we conducted a 391-km north to south transect (mean annual precipitation < 600 mm) survey in the Loess Plateau of China, to investigate the biogeographic distributions of autotrophic bacteria (RubisCO cbbL and cbbM genes) and the environmental drivers across different latitude sites with clear vegetational and climatic gradients. Results and Discussion: The soils in northern region with lower precipitation are dominated by grassland/forest, which is typically separated from the soils in southern region with higher precipitation. The community structure of autotrophic bacterial cbbL and cbbM genes generally differed between the soils in the southern and northern Loess Plateau, suggesting that precipitation and its related land use practices/ecosystem types, rather than local soil properties, are more important in shaping the soil autotrophic microorganisms. The cbbL-containing generalist OTUs were almost equally abundant across the northern and southern Loess Plateau, while the cbbM-containing bacterial taxa were more prevalent in the low precipitation northern region. Such differences indicate differentiate distribution patterns of cbbM-and cbbL-containing bacteria across the north to south transect. Our results suggest that the community composition and the differentiate distributions of soil cbbL-and cbbM-containing bacterial communities depend on precipitation and the related ecosystem types in the north to south transect in the Loess Plateau of China.